Pleasure principles: A review of research on hedonic consumption - Alba, Joseph W.; Williams, Elanor F. (Journal of Consumer Psychology, 2013)
AbstractThirty years ago, Hirschman and Holbrook (1982) advocated greater attention to hedonic consumption and the myriad ways in which consumers seek pleasure and enjoyment. A thorough review finds that the topic has much appeal and that consumer research has made significant progress toward understanding some of its parameters. However, many questions remain unanswered, particularly with regard to understanding the sources of pleasure, the manner in which consumers seek it, and the ways in which consumers might alter their hedonic consumption decisions to maximize pleasure and happiness. We assess three decades of research on hedonic consumption, emphasizing areas of greatest potential for future exploration.